Sexism and Stereotypes in Modern Society: The Gender Science of Janet Taylor Spence.
DOI: 10.1037/10277-009
|View full text |Cite
|
Sign up to set email alerts
|

Gender and self-esteem: A meta-analysis.

Abstract: ne of the many questions explored by Janet Taylor Spence and 0 her colleagues concerns the relationships among gender, selfesteem, and so-called "masculine" agentic personality characteristics and "feminine" communal personality characteristics. In what has been considered a surprising finding, Spence's research indicates that the same relationships are typically observed in both men and women: Possession of masculine attributes is substantially and positively correlated with self-esteem, whereas possession of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
40
0
5

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 54 publications
12
40
0
5
Order By: Relevance
“…Previous research has found modest gender differences in self-esteem levels such that men often report slightly higher levels of global self-esteem (Kling et al 1999;Major et al 1999;Twenge and Campbell 2001) and certain domain-specific self-evaluations than women (e.g., appearance; Gentile et al 2009). For the present study, however, gender differences did not emerge for self-esteem (M Men =3.94, M Women =3.99; t[179]=.46, ns).…”
Section: Resultsmentioning
confidence: 97%
“…Previous research has found modest gender differences in self-esteem levels such that men often report slightly higher levels of global self-esteem (Kling et al 1999;Major et al 1999;Twenge and Campbell 2001) and certain domain-specific self-evaluations than women (e.g., appearance; Gentile et al 2009). For the present study, however, gender differences did not emerge for self-esteem (M Men =3.94, M Women =3.99; t[179]=.46, ns).…”
Section: Resultsmentioning
confidence: 97%
“…Finally, for exploratory purposes, we related implicit selfesteem to a number of variables that have been shown to relate to explicit self-esteem such as gender (Major, Barr, Zubek, & Babey, 1999), mood (e.g., Dua, 1993;Tarlow & Haaga, 1996), academic achievement (Khalid, 1990;Newbegin & Owens, 1996), and physical health (e.g., Antonucci & Jackson, 1983;Carroll & Buhrow, 1994;O'Connor & Vallerand, 1998;Vingilis, Wade, & Adlaf, 1998). We also related implicit self-esteem to participants' use of the word /, which is thought to indicate self-focused attention (e.g., Kernis, Grannemann, Richie, & Hart, 1988;Mullen, Chapman, & Peaugh, 1989;Wegner & Giuliano, 1980).…”
Section: Overview and Research Questionsmentioning
confidence: 99%
“…These reports and books focused on gender-related classroom and school inequities and girls' supposed loss of self-esteem during adolescence. Despite findings from two meta-analyses shortly thereafter that self-esteem gender differences were relatively small and dependent upon ethnicity (Kling et al 1999;Major et al 1999), many female political leaders and social commentators, including feminists who had attended women's colleges, came to view girls' schools as safe havens from the sexism of coeducational classrooms. That is, the exclusion of boys from classrooms was viewed as an effective and acceptable means of promoting gender equality by improving girls' academic achievement and mental health (Weil 2008).…”
Section: Causes Of the Contemporary Rise In Single-sex Schoolingmentioning
confidence: 94%